Effects of different charcoal-containing whitening toothpastes on color and surface roughness of a supra-nanofilled composite resin - Meltem Nermin Polan; Sevil Gurgan (BMC Oral Health)
Abstract Background To evaluate the impacts of various charcoal-containing whitening toothpastes on color stability and surface roughness of a supra-nanofilled composite resin. Methods A total of 105 disc-shaped specimens were fabricated using a supra-nano spherical-filled composite resin and immersed in a coffee solution to induce staining. Color and surface roughness were measured before (T0) and after staining process (T1). The specimens were randomly allocated into seven groups (n = 15): a negative control (Distilled water, DW), a positive control (Colgate Total 12, CT12), and five groups treated with charcoal-containing whitening toothpastes: Colgate Optic White (COW), Curaprox Black Is White (CBW), R.O.C.S. Black Edition Whitening (ROCS), Ipana 3D White (IPW), and Signal Nature Elements Charcoal (SNE). Brushing was performed using an electric toothbrush three times per day for 30s over a two-week period, followed by final color and surface roughness measurements (T2). Statistical analyses were performed using one-way ANOVA, Kruskal–Wallis, Tukey’s HSD, Tamhane’s T2, and Dunn’s tests (p < 0.05). Results Color alterations (ΔE00) in all groups treated with charcoal-based whitening toothpastes exceeded the clinical acceptability threshold. However, no statistically significant differences in ΔE00 were noted among these groups (p > 0.05).The SNE group exhibited significantly higher ∆b values than the COW and CBW groups (p < 0.05), while the CBW group presented considerably lower ΔL values than the COW, IPW, and SNE groups (p < 0.05). A significant increase in surface roughness ​​was detected in all groups exposed to charcoal-based whitening toothpastes (p < 0.05),with statistically significant variations observed among groups (p < 0.05). Conclusions Charcoal-containing whitening toothpastes effectively reduced coffee-induced discoloration on composite resin surface while causing a significant increase in surface roughness. The toothpastes used exhibited similar effects on color change but showed variations in surface roughness among groups.